Implementasi Sistem Pengawasan Perlindungan Hukum Terhadap Pembeli Kosmetik Secara On-Line (SISWAS-PK) - Asriati Asriati; Muh. Zulkifli Muhdar; Asrianty Anggreany Mangarengi (Lembaga Layanan Pendidikan Tinggi (LL DIKTI) IX Sulawesi, 2019)
Abstract: The purpose of research to analyze and explain the implementation of a monitoring system legal protection to buyers in on-line, cosmetics to analyze and explain faktor-faktor that affects the implementation of the supervision of consumer protection.The type of research the kind of research that is used is empirical research, namely research, field by means of conducting data collection in the field based on a problem that were submitted in this research. The implementation of the system of monitoring the protection of the law to their customers cosmetics in an online manner which was carried out by the world largest oil consumers protection division for monitor goods distribution from the local office of industry and trade south sulawesi and the porch or vestibule food and drug monitoring the city of makassar to be channeled to has not yet been optimized, the factors that affects the implementation of the supervision of consumer protection is subtansi law pertaining to rules designed to weed out act which regulates regional consumer protection, instrumentality used in the supervision of consumer protection and the only implementing body for the supervision of challenges to his own party with both the socialization to the general public now about the offering that the world largest oil consumers complaints in an online manner.